Hearing Early Opens More Doors: Long-Term Effects of Age at Implantation on Metaphor Comprehension in Adolescents and Young Adults With Cochlear Implants. - Dahlby-Skoog, Malin; Kalandadze, Tamara; Karltorp, Eva; Lyxell, Björn; Löfkvist, Ulrika (Journal of Speech, Language & Hearing Research, 2025)
Purpose: There is solid evidence that an early age at cochlear implantation, which reduces the period of auditory deprivation, positively impacts early spoken language development. However, there is an urgent need for more research to understand the long-term effects of early implantation on higher linguistic skills, such as metaphor comprehension. In this study, we explored metaphor comprehension in Swedish-speaking adolescents and young adults with cochlear implant (CI), compared to that of typically hearing peers, as well as its relationship with the age at first CI. Method: The participants consisted of 39 individuals who received CI before 30 months of age (M = 16.9 years, mean age at implant = 15.7 months) and a group of 27 individuals with typical hearing (M = 14.9 years). To assess metaphor comprehension, we developed a multiple-choice task that was administrated verbally. Standardized tests were used to evaluate vocabulary, reading skills, and nonverbal cognitive skills. Results: No significant differences were found in metaphor comprehension or other linguistic or cognitive skills between individuals with CI and the typically hearing peers. Further analysis indicated a moderate negative correlation between metaphor comprehension and age at implantation and other linguistic skills. Conclusions: Early-implanted children develop metaphor comprehension comparable to their typically hearing peers, with earlier age at implantation being associated with better metaphor comprehension in adolescence. However, age at implantation only partially explains the variation in metaphor comprehension abilities. Further research is needed to identify other factors that influence the development of metaphor comprehension in individuals with CI.